2007
DOI: 10.1002/ps.1351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glyphosate on soil microbial communities and its mineralization in a Mississippi soil

Abstract: Transgenic glyphosate-resistant (GR) soybean [Glycine max (L.) Merr.] has enabled highly effective and economical weed control. The concomitant increased application of glyphosate could lead to shifts in the soil microbial community. The objective of these experiments was to evaluate the effects of glyphosate on soil microbial community structure, function and activity. Field assessments on soil microbial communities were conducted on a silt loam soil near Stoneville, MS, USA. Surface soil was collected at tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 31 publications
11
74
1
1
Order By: Relevance
“…By contrast, the P. putida species were more sensitive to the glyphosate-containing growth media whereby, compared to growth in the absence of glyphosate, the strain S12 experienced up to 100% growth inhibition but the strain KT2440 only exhibited up to about 23% growth inhibition (Figure 2). There have been conflicting results on the adverse effects of glyphosate exposure on soil microbial community structure (Weaver et al, 2007;Johal and Huber, 2009;Kremer and Means, 2009;Mijangos et al, 2009;Barriuso et al, 2011;Duke et al, 2012). Our results here support the proposal that species-dependent sensitivities to glyphosate led to the observed change in microbial community structure in soils amended with glyphosate (Ratcliff et al, 2006;Newman et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…By contrast, the P. putida species were more sensitive to the glyphosate-containing growth media whereby, compared to growth in the absence of glyphosate, the strain S12 experienced up to 100% growth inhibition but the strain KT2440 only exhibited up to about 23% growth inhibition (Figure 2). There have been conflicting results on the adverse effects of glyphosate exposure on soil microbial community structure (Weaver et al, 2007;Johal and Huber, 2009;Kremer and Means, 2009;Mijangos et al, 2009;Barriuso et al, 2011;Duke et al, 2012). Our results here support the proposal that species-dependent sensitivities to glyphosate led to the observed change in microbial community structure in soils amended with glyphosate (Ratcliff et al, 2006;Newman et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…The reason for this observation was borne of the fact that the degradation of glyphosate was more rapid in the wet season than in the dry season which conforms to the finding of Smith and Aubin (1993) that the relative dryness of the soil in dry seasons may result to slow dissipation of glyphosate herbicide. Weaver et al (2007), reported that glyphosate herbicide dissipates rapidly when applied to moist soil than dry soil.…”
Section: Discussionmentioning
confidence: 99%
“…No major changes in community structure, assessed by CLPP and PLFA, occurred with application of field rate concentrations of glyphosate in soils from two pine plantations in California (Ratcliff et al, 2006). Both higher abundance of PLFA biomarkers of gram-negative bacteria (Weaver et al, 2007;Lancaster et al, 2009) and fungal to bacterial biomass ratios ) have been reported in glyphosate-treated soils. In a recent study, Zabaloy et al (2009) reported minor effects of glyphosate on sole C sources utilization with BDOBS.…”
Section: Microbial Community Structurementioning
confidence: 92%
“…Unintended consequences of herbicide applications may be the reduction of sensitive populations and/or stimulation of a certain microbial group with or without detriment to co-existing microbial populations that may compete for available resources. Several investigations that used culture-independent methods reported only slight, short-lived effects of field levels of glyphosate (Weaver et al, 2007;Accinelli et al, 2007) and 2,4-D (Chinalia & Killham, 2006;Macur et al, 2007;Vieublé-Gonod et al, 2006) on microbial communities. No major changes in community structure, assessed by CLPP and PLFA, occurred with application of field rate concentrations of glyphosate in soils from two pine plantations in California (Ratcliff et al, 2006).…”
Section: Microbial Community Structurementioning
confidence: 99%